Effects of nozzle structural parameters on yarn hairiness in jetring spinning system - Gulsevincler, Ekrem; Usal, Mustafa Resit; Yilmaz, Demet (Informa UK Limited, 2020)
In this study, the effects of the performance of air nozzles called jetring, which can be connected to a conventional ring spinning machine, over the yarn hairiness values were investigated. To det...